Estudio de los daños y refuerzos necesarios para la recuperación del techo de la iglesia de Salsipuedes-Córdoba-Argentina - Gómez, J. L.; Klein, K.; Montiel, G. (Revista ALCONPAT, 2014)
Salsipuedes The Church of the Province of Cordoba was built in 1875 and its roof is formedby a wooden structure, reticulate beams and straps which support ceramic arches tile mortarlayer and tiling LegguardsThe Church is disabled as a precaution due to the appearance of cracks in the grid bars andbreaking away of pieces of masonry near the support of the main beams. In this work westudy the stress state of the grid bars and support the realization of the main beams in themasonry walls.Confirmed the high value of the working stresses of the bars with pathologicalmanifestations, as well as inadequate support system in the masonry, projectingreinforcements necessary for safe operation of the structure with a degree of security..Keywords: Wooden structures, pathology, patrimony